MAKING THE WORLD WONDER FREE 7 APPLICATION PROGRAM USING MACROMEDIA FLASH 5.0 - Herlina Hidayati; Linda Wahyu Widianti, Skom, MMsi (Jurnal Sistem Informasi, 2005)
Ensikopedia of today is not a new thing anymore. Nearly all the world knew him. Encyclopedias are also a collection of knowledge resources. In free we can  search wide range of information both old and new, such as world history, famous figures, and many others.  Seven wonders of the world, a historic building located in seven different countries. Scientific Writing aims to create a free 7 wonders of the world that can be used as a means of information for all people in  general and in particular to the pre-school children basic and elementary schools. In scientific writing will discuss how to make a free 7 wonders of the world is simple and also attractive. Also included too little information about the seventh article of  the building. The materials obtained from several books of history, geography and also the internet.  Making free use of application program Macromedia Flash 5.0, Photoshop 6.0 to edit images, and Sound Forge 4 for sound editing.